2006
DOI: 10.1055/s-2006-924748
|View full text |Cite
|
Sign up to set email alerts
|

Nonparasitic Splenic Cysts in Children: A Multicentric Study

Abstract: Over the last two decades, the surgical treatment of NPSCs has changed from a formerly customary total splenectomy to spleen-conserving procedures, such as total cystectomy with or without partial splenectomy or partial cystectomy. These therapeutic modalities can be performed laparoscopically, if technically possible. Fenestration or deroofing of the cyst resulted in a high recurrence rate (7/9).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 16 publications
0
42
0
4
Order By: Relevance
“…Czauderna et al [58] reported that in a study of 50 children with nonparasitic splenic cysts, laparoscopic removal of the cyst was associated with a higher rate of complications and recurrence than open surgery.…”
Section: Splenectomy For Benign and Malignant Disordersmentioning
confidence: 99%
“…Czauderna et al [58] reported that in a study of 50 children with nonparasitic splenic cysts, laparoscopic removal of the cyst was associated with a higher rate of complications and recurrence than open surgery.…”
Section: Splenectomy For Benign and Malignant Disordersmentioning
confidence: 99%
“…CT and magnetic resonance imaging are of choice in the diagnosis and planning of the surgical strategy 3,8,9 . In large cysts, CT with 3-D reconstruction may show the relationship with hilum vessels and remaining spleen size.…”
Section: Discussionmentioning
confidence: 99%
“…A European multicentre case series over 25 year period treating 50 children with NPSC consisted of 7 children managed by partial cyst excision. They had a median operating time of 90 min and 12 months median follow up resulting in 44% recurrence (Czauderna et al, 2006). Two other large case series with 13 and 14 patients described symptomatic recurrence rates of 7.6 and 7.1% respectively (Langer et al, 2008;Schier et al, 2007).…”
Section: Discussionmentioning
confidence: 99%